FIELD EVALUATION OF VARIOUS CHEMICALS AND BIOAGENT AGAINST BACTERIAL BLIGHT OF DESI COTTON (Journal of Plant Disease Sciences, 2024)
Bacterial blight cause yieldlossesincotton cropworldwide. Lossesare lesswhen only leaves are infected but when stem lesions are formed, the losses may be high as upto 90%. The experiment was planned to evaluate the twelve spray treatments viz. 10 chemicals, one bioagent and one untreated control in natural field conditions against Xanthomonas axonopodis pv. malvacearum causing bacterial blight of cotton in Desi variety. First Spray wasgiven at first apperance of disease and subsequent twosprays were given at 15 days interval. Observations on disease incidence (PI) and disease severity (PDI) were recorded before one day of each spray.Amongsthe chemicals and bioagent tested the results obtained after third spray indicated that significantly lowest disease incidence of 20.84 % was recorded by the treatment streptocycline + copper oxychloride followed by the treatment streptocycline + carbendazim (20.92%), streptocycline + copper hydroxide (20.96 %), bordeaux mixture (21.35 %), but all four treatmentsfoundatpar in successionasagainst the unsprayed control 51.18 per cent (PI) and lowest disease severity of 10.22 % was recorded by the treatment streptocycline + Copper oxychloride followed by the treatmentstreptocycline + carbendazim (11.33 %), streptocycline + copper hydroxide (13.00 %), streptocycline (13.45 %).
Keywords: Desi Cotton; Bioagent; Chemicals; Xanthomonas; axonopodis malvacearum, pv.